Executive functions and personality traits of juvenile myoclonic epilepsy patients: single-center experience of 23 cases - MİDİ, İPEK (My University, 2022)
Background/aim: Juvenile myoclonic epilepsy (JME), which is a fairly common form of generalized epilepsy syndrome has attracted attention by providing focal findings in some electrophysiological, neuropsychological, and neuroimaging studies. These findings are considered to be based on frontal lobe dysfunction. Furthermore, it is known that Cluster B personality disorders that are related to impulsive behavior are frequently seen in JME patients. Materials and methods: In this study, 23 JME patients and 20 healthy control subjects were included. All subjects were assessed using neuropsychological tests for executive functions and the Temperament and Character Inventory (TCI) for personality traits. Results: JME patients performed poorly in the digit span test and the Stroop Color and Word Interference Test. When the TCI scores were compared, there was no significant difference between the patients and the control subjects compatible with the literature. In addition, cooperativeness-character dimension (C1-social acceptance) scores were significantly lower in the patient group. Conclusion: Our findings support that JME patients have frontal lobe dysfunction. Although several studies are available in the literature, no significant results related to personality traits were detected. Key words: Juvenile myoclonic epilepsy, executive functions, temperament and character inventory
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Juvenile myoclonic epilepsy; executive functions; temperament and character inventory; TEMPERAMENT; Juvenile myoclonic epilepsy; executive functions; temperament and character inventory